Challenges and Opportunities for Innovation in Implementing Electronic Medical Record (EMR) at Indonesia First-level Army Health Facilities - Anna Triwijayati; Dea Amelia Aditya Winata; Seno Aji Wahyono (International Journal of Public Health Excellence (IJPHE), 2026)
This study aims to explore the challenges, efficiency, and innovation opportunities with the implementation of Electronic Medical Records (EMR) at Indonesia first-level army health facilities specifically Air Defense Artillery Center Clinic (Pusdikarhanud). This research adopted a qualitative approach using a case study method through semi-structured interviews with nine informants, consisting of seven clinic staff and two patients. In addition, participatory observation allowed the researcher to comprehend the subjective meanings behind individual actions and social interactions in the context of EMR usage. The findings indicate that the EMR implementation at the Pusdikarhanud Clinic faced several challenges related to technology infrastructure, staff training, data security and privacy, as well as integration with other systems. However, EMR implementation also brings efficiencies in coordination and collaboration among service units, clinic operations, and the enhancement of healthcare service quality. Furthermore, various innovation opportunities are identified, such as improving technology infrastructure, developing additional features in EMR, and integrating with other healthcare service systems. Theoretical implications of this study are the importance of systems-based approaches in health management and the potential of EMR as a tool to enhance efficiency and healthcare service quality. The practical implications include recommendations for the Pusdikarhanud Clinic to improve technology infrastructure, staff training, data security, and system integration, as well as policy recommendations for the government in standardizing EMR implementation, providing financial support, and developing technology infrastructure. Therefore, this study provides valuable insights for healthcare practitioners, policymakers, and researchers in understanding the challenges and opportunities of EMR implementation in health management transformation.